When Stars are Scattered - Jamieson, Victoria; Mohamed, Omar (Social worker); Geddy, Iman (New York : Dial Books for Young Readers, 2020)
"Omar and his younger brother Hassan live in a refugee camp, and when an opportunity for Omar to get an education comes along, he must decide between going to school every day or caring for his nonverbal brother in this ... portrayal of family and daily life in a refugee camp"--
Keywords: Mohamed, Omar -- (Social worker) -- Comic books, strips, etc -- Childhood and youth; Mohamed, Omar -- (Social worker) -- Cartoons and comics; Refugees -- Biography -- Somalia; Refugees -- Biography -- United States; Refugee camps -- Comic books, strips, etc -- Kenya; Brothers -- Comic books, strips, etc; Refugees -- Cartoons and comics; Refugee camps -- Cartoons and comics; Brothers -- Cartoons and comics; Cartoons and comics; Biographical comics; Nonfiction comics; Graphic novels; Comics (Graphic works)